Por uma reconstrução do/no ensino remoto – rascunhos e borrões em um fazer inclusivo no ensino superior - Aguiar, Ana Lúcia Oliveira (2022)
This article is about remote teaching and focuses specifically on inclusion in Higher Education. The relevance of this study is based upon reflection on the daily lives of disabled students concerning the challenges of remote education and more precisely the use of digital resources in the learning process. Inclusion policies bring to mind the concept of impairment in terms of attitudinal, conceptual and procedural barriers. There are three aspects related to this study: the first one is about the legislation for disabled people, the second one focuses on theoretical discussions about the barriers of communication; assistive technology, inclusion, and remote learning. The last one is the development of strategies for inclusion focused on learning. We’ve noticed reformulations in the educational practice in remote teaching time, with new initiatives, new practices, collaborative experiences and actions that promote listening, to observe the paths of people with disabilities. We are aware that attention to inclusion policies, the reading on the concept of inclusion, and the experience, based on students’ experiences, are central dimensions for the formation of personalized and flexible remote teaching. Alterity is a path that involves experience from self-reflection to be able to think of others, considering that each experience is unique for each individual.